Identification and Antifungal Susceptibility Pattern of Candida Isolates Recovered from Urine and Blood Specimens from Patients Admitted in Wards of a Tertiary Care Hospital, North Delhi - Sanjay Jain; Shilpa Khatri; Manoj Kumar; Tanisha Bharara; Abhishek Yadav (Masters Program in Public Health, 2024)
Background: Candida species are responsible for various clinical infections ranging from mucocutaneous infection to life-threatening invasive diseases. Increased resistance to antifungal drugs during the last decade has become a serious concern. Therefore, identification of Candida up to species level and its antifungal susceptibility testing is very important in the management of Candida infections. This study aimed to identify these organisms and study their susceptibility patterns.Subjects and Method: A retrospective study was conducted over 9 months (July 2022 to March 2023) from urine and blood samples collected from 80 IPD patients admitted to various wards of Hindu Rao Hospital. The samples were selected based on their growth on blood agar. The variables of interest are the different species of Candida and susceptibility to antibiotics. Identification of Candida species was done by Gram stain, Germ tube formation test, color on HiCrome Candida agar medium, chlamydospore formation on corn meal agar, and VITEK 2 Compact System. The MICs were interpreted according to the CLSI guidelines 2022.Results: 47 and 33 of urine and blood cultures were positive for Candida species respectively. Most of the isolates were from the Paediatric ward (28.75%), followed by the Medicine ward (27.5%). The most common species was C. tropicalis (56.25%) followed by C. albicans (23.75%). Most species of Candida were sensitive to amphotericin B, fluconazole, voriconazole, caspofungin, micafungin, and flucytosine except Candida albicans which showed 100% resistance to amphotericin B and Candida krusei which showed 66% sensitivity to voriconazole and 33% to caspofungin.Conclusion: Candida colonization has a considerable prevalence among patients hospitalized in our hospital. The species identification of Candida isolates along with their antifungal susceptibility pattern can help the clinician in better treatment of patients with candiduria and candidemia. Keywords: Candida, bloodstream infection, minimum inhibitory concentration